Streamlined life cycle CO2 emission assessment of sewage treatment in Taiwan - Yu, Sheng Chang (Universiti Kebangsaan Malaysia, 2015)
Sewage treatment is an important issue in a country for public health and environmental protection. The treatment process not only consumes energy but also emits CO2. In this research, the idea of streamlined life cycle assessment was applied. The CO2 emission from sewage treatment was assessed from direct energy consumption of four major sewage treatment plants in Taiwan. The results showed that the CO2 emission at in-plant sewage treatment stage takes more than 95% of total CO2 emission for most plants. The results suggested that CO2 emission of sewage treatment can be calculated from energy consumption at in-plant sewage treatment stage to simplify the calculation. The CO2 emission of sewage treatment was then assessed from sewage plants in Taiwan using in-plant electricity consumption. The unit CO2 emission of sewage treatment in Taiwan is 0.216 kg-CO2/m3. This database will be an important reference for water resource research and future government environmental policies.